To compare NIHSS scoring system for outcome in anterior and posterior circulation stroke - Aishwarya Ram; Mamatha Tittamegalapalya Ramalingaiah; Sheetal Rudra Naik (Asian Journal of Medical Sciences)
Background: The arterial territory affected in the stroke significantly affects the prognosis and outcome. National institutes of health stroke scale (NIHSS) score widely used significantly differs between anterior and posterior circulation stroke.